Relevance of Ethical Norms and Religious Values to Realize a Harmonious and Dynamic Social Life - Nisa, Habibatun; Hidayat, Rahmad; Samiun, Budi (Pancasila International Journal of Applied Social Science, 2023)
Islamic thinkers nor thinker West contemporary You're welcome realize that man moment This is at on peak crisis Which I, Where presence science and technology modern has reduce existence humanity as potency ideal and strength in designing civilization modern. In address circumstances it, is needed attitude which more appreciative and active in enable values ethics and religion in life social and social. Speak problem ethics and religion No regardless from problem life man That Alone. With such is the relationship between ethics with religion very tight relation, ie exists each other fill and support between One with Which other. Both of them there are similarities base, ie you’re welcome investigate and determine size Good and bad with see on charity deed man. by him That, ethics And religion be a need life Which own function And still apply And needed in life social, for example in matter politics, law, economy, culture etc. Ethics support existence religion, where ethics able assist humans in using the mind to solve problems. Basic ethics self on argument rational whereas religion base on revelation Lord which the truth absolute (absolute).